Post-match recovery responses in Italian Serie A youth soccer players: effects of manipulating training load 48 h after match play - Franceschi, A.; Robinson, M.; Owens, D.; Brownlee, T.; Connolly, D.; Coutts, A.; Ferrari Bravo, D.; Enright, K. (European Journal of Sport Science, 2025)
This study described the recovery responses following match play and examined the effects of manipulating training load 48 h post-match in Italian Serie A youth soccer players. Forty-eight players were assessed using the countermovement jump (CMJ), isometric posterior-chain muscle test (IPC), muscle soreness and fatigue before (pre) and after (0.5 h post, 48 h post and 72 h post) a match. At 48 h post-match, players were randomly assigned to a complete training (CT; n = 26) or a reduced training (RT; n = 22) group. Recovery differences were analysed between time points and training groups, with training loads quantified on match day (MD) and match day plus two (MD + 2). Recovery measures were impaired immediately post-match (p < 0.05). IPC and muscle soreness demonstrated incomplete recovery 48 h post-match (p < 0.05), whereas CMJ and fatigue returned to baseline (p > 0.05). Training load on MD did not differ between groups (p > 0.05), whereas the CT group had higher load on MD + 2 compared to RT (p < 0.05). A significant time × group interaction was observed for CMJ height and IPC measures (p < 0.05), with reductions in physical performance observed in the CT group from 48 to 72 h post-match (p < 0.05). A youth soccer match acutely impaired physical performance and recovery status, with prolonged and incomplete recovery of hamstring force and elevated muscle soreness 48 h post-match. A high-volume and high-intensity session administered 48 h post-match negatively influenced physical performance compared to a moderate training session.